Outcomes of liver transplantation of hepatoblastoma: single-center data in mainland China - Huang, Hongting; Li, Linman; Zhu, Jianjun; Xu, Dongwei; Wan, Ping; Qiu, Bijun; Zhang, Jiaxu; Yang, Yongkang; Zhao, Jie; Zhang, Jianjun; Luo, Yi; Feng, Mingxuan; et al. (Frontiers in Pediatrics, 2025)
ObjectiveHB is the most common liver malignancy in children. Giving the rarity of the research reporting outcomes of LT for HB in China, updated long-term data are needed. The primary objective was to evaluate the outcomes of liver transplantation in HB. The secondary objective was to assess the clinical parameters that influence the outcomes of liver transplantation in HB.MethodsWe retrospectively analyzed the dataset of a single-center cohort from RJ-SJTUM. Outcomes were OS and PFS. Cox proportional hazard models were used to estimate mortality adjusted HRs with 95% CIs.ResultsRJ-SJTUM has accounted for 68.5% of the total cases in China since 2019. The 5-year PFS and OS rates were 63.6% and 84.6% respectively. AFP ≥13,686.5 ng/ml before LT was an independent risk factor for PFS (P < 0.001), and distal metastasis before LT was an independent risk factor for OS (P = 0.028). All patients received post-LT chemotherapy, and two patients experienced severe liver injury. Patients with localized tumor recurrence after LT had favorable outcomes if radical resection of the recurrence was achieved. Sirolimus played a role in prolonging the survival of patients with recurrent HB after LT (P = 0.0307).ConclusionLT achieved favorable outcomes for patients with locally advanced hepatoblastoma. This study suggests that a judicious patient selection to exclude patients with high-risk predictors, as well as standardized postoperative management is critical in this process.